A REVIEW: A MODEL of CULTURAL ASPECTS for SUSTAINABLE PRODUCT DESIGN - Ihwan Ghazali; Salwa Hanim Abdul Rashid; Siti Zawiah Md Dawal; Alva Edy Tontowi; Hideki Aoyama (Spektrum Industri, 2012)
Product design stages are important to consider critically in production. Generally, product design that shall be created by designer, should consider what the customer wants and needs. Nowadays issues, product design does not only consider the â€œwants and needsâ€ of user, but also how the design can be created by embedding sustainability aspects in the product. Culture is also one of the important aspects which need to be considered in product design as culture affects the way users respond to the product. This paper aims to develop a new model for design development, in which the aspects of culture are incorporated into sustainable product design. By reviewing the existing literature, the authors attempt to identify the gaps of the existing papers, which illustrate how culture affects sustainable product design. Recent papers have only shown that culture influences product design, but they do not explore sustainability and the culture aspects in product design. Due to these gaps, it is therefore important to create a model which will assist designers to elicit sustainable product design based on cultural aspects. In summary, designers need to reflect on the â€œwants and needsâ€ of users. The framework presented in this paper can be integrated into designersâ€™ and companiesâ€™ decision-making during product design development. Keywords: Model, Culture, Sustainable, Product design, Product Development.